Efficacy of intranasal naloxone compared to other administration routes in prehospital opioid overdose management and beyond: a narrative review - Luigi Venuso; Francesco Ricciardi; Antonio Del Prete; Michele Virgolesi; Gianluca Pucciarelli; Luigi Langella; Teresa Rea (Emergency Care Journal)
Drug-related deaths in Italy, especially from opioid overdoses, increased by 6% among individuals aged 15-34 from 2014 to 2018. Opioid-related deaths rose by 6.6% in the 15-24 age group and by 5.4% in the 25-34 age group during this period. There is limited data on the effectiveness of different naloxone administration routes—intranasal (IN), intramuscular (IM), and intravenous (IV)—and no established guidelines for prehospital overdose management. Timely intervention is crucial to reduce overdose mortality. This review aims to assess the effectiveness of naloxone administration methods in opioid overdoses, focusing on prehospital settings and comparing IN, IM, and IV routes. A narrative review was conducted in accordance with PRISMA guidelines. The search included terms such as “naloxone,” “opioid overdose,” “intranasal administration,” and “prehospital emergency care,” with Boolean operators to refine the scope. The study selection was guided by the PICO framework (population, intervention, comparison, outcome). Studies were assessed for quality using the Dixon-Woods tool, and inclusion/exclusion criteria were applied. Studies will be selected based on populations treated with naloxone administered via intranasal, intramuscular, or intravenous routes, focusing on comparisons between these formulations in terms of onset time and intervention effectiveness. Out of 111 studies, five met the eligibility criteria. These studies showed that intranasal naloxone achieves higher plasma concentrations than intramuscular doses but with slower absorption and longer peak times. Additionally, intramuscular naloxone results in faster respiratory recovery and requires fewer doses. Intranasal naloxone has a bioavailability of 46.8% to 50.8% compared to intravenous naloxone, with efficacy outcomes varying by administration route. The review shows that intranasal naloxone, especially at a 2 mg dose, achieves plasma levels similar to intramuscular formulations and has linear pharmacokinetics across dosages. While its bioavailability is lower (46% to 50%) compared to intravenous administration, it is a safer and more practical option for non-clinical settings. Although intramuscular and intravenous routes work faster, the slower absorption of intranasal naloxone may help reduce withdrawal symptoms, supporting gradual dosing strategies. These findings emphasize the need for further research on optimizing naloxone dosing for synthetic opioid emergencies. This review highlights intravenous naloxone as the most effective route for opioid overdose treatment, with intramuscular and intranasal routes offering practical alternatives in prehospital settings. Intranasal naloxone, despite its lower bioavailability, provides a non-invasive option suitable for lay responders. Gradual dose escalation is recommended to minimize withdrawal symptoms. The increasing prevalence of synthetic opioids underscores the need for updated clinical guidelines on naloxone dosing and administration routes.